Economic viability of rooftop photovoltaic systems in the middle east and northern African countries. (December 2020) - Alrawi, Omar F.; Al-Ghamdi, Sami G.
Abstract: Renewable energy sources and the possible sustainability that can be achieved through them has become a common discourse in the world today. The Middle East and Northern African countries have high potential to benefit from large scale renewable energy projects. These nations may initiate or permit the use of residential rooftop photovoltaic (PV) systems in the near future. However, data regarding system design, grid compatibility, and consumption of energy produced through rooftop photovoltaic systems is insufficient. The supporting policies and a feed-in tariff lack, thereby creating more research and development issues. Therefore, this research study aims to use the ten most populated nations in the Middle East and Northern Africa to (1) compare the use of rooftop PV systems in ten populated cities and (2) to evaluate the economic viability of rooftop PV systems under varying policies and electricity rate schemes. The findings of the study can help policymakers understand the application of rooftop PV systems in the Middle East and Northern African countries. The study, the first of its kind, uses an economic model to evaluate rooftop PV systems in ten identical houses in ten of the most populated cities in the Middle East and Northern African countries.